Efficacy of different techniques for diagnosis of pyometra in female dogs - PANDE, NISHI; PRABHAKAR, S; GANDOTRA, V K; HONPARKHE, M; NANDA, A S (The Indian Journal of Animal Reproduction, 2023)
Pyometra in female dogs is a polysystemic diestrual disorder which if not treated can induce high mortality. A definite diagnosis ofpyometra in bitches becomes a challenge on certain occasions. A comparative study of different techniques for the diagnosis ofpyometra was, therefore, made in twenty bitches with clinical symptoms ofpyometra. Uterine enlargement (>1.0 cm diameter) through abdominal palpation was found to be confirmatory in 75 per cent of the pyometritic bitches. Only 9 out of20 bitches had neutrophilia (>77 %) characteristic ofpyometra. Plain radiography could detect uterine enlargement in 9 out of 19 pyometra-affected bitches. Ultrasonography was found to be conclusive for diagnosis of pyometra in 16 out of 18 bitches.The results thus, suggested abdominal palpation and ultrasonography along with clinical history as effective techniques for the diagnosis of pyometra.